2012
DOI: 10.1002/hep.25921
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of residual hepatitis C virus in presumed recovered subjects

Abstract: Recent studies have found hepatitis C virus (HCV) RNA in peripheral blood mononuclear cells (PBMCs) of the majority of presumed recovered subjects. We investigated this unexpected finding using samples from patients whose HCV RNA and anti-HCV status had been serially confirmed. HCV RNA was detected in PBMCs from 66/67 chronic HCV carriers. Subpopulation analysis revealed that the viral load (log copies/106 cells) in B cells (4.14 ± 0.71) was higher than in total PBMCs (3.62 ± 0.71, p<0.05), T cells (1.67 ± 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 32 publications
1
31
2
Order By: Relevance
“…Mohamad et al (26) described that 26% of the SVR patients had a detectable level of HCV RNA in PBMC 6 month after completion of treatment. The current and all the mentioned studies, except the study done by Fujiwara et al (25), found HCV RNA in the blood cells of the patients treated with IFN-based treatments. The difference in the reported rate of detection by these studies was mainly justified by the following points; different time points for detection of HCV RNA in PBMC after achieving SVR, various methods for detection of HCV RNA in the PBMC samples and different host and viral parameters of patients included.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Mohamad et al (26) described that 26% of the SVR patients had a detectable level of HCV RNA in PBMC 6 month after completion of treatment. The current and all the mentioned studies, except the study done by Fujiwara et al (25), found HCV RNA in the blood cells of the patients treated with IFN-based treatments. The difference in the reported rate of detection by these studies was mainly justified by the following points; different time points for detection of HCV RNA in PBMC after achieving SVR, various methods for detection of HCV RNA in the PBMC samples and different host and viral parameters of patients included.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast to our study, Inglot et al (24) found 6.1% of patients with SVR to PegIFN and RBV had HCV RNA negative strand in their PBMC samples 24 weeks after termination of treatment. In another study, Fujiwara et al (25) revealed that residual HCV RNA was not detected in plasma or PBMCs of any spontaneous or treatmentrecovered subjects suggesting that the classic pattern of recovery from HCV infection is generally equivalent to viral eradication. Gallegos-Orozco et al (23) included 25 patients with SVR to PegIFN and RBV treatment 6 -56 months (mean, 22 months) after the end of treatment and looked for HCV RNA in their PBMC samples following cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…HCV uses various receptors for entry allowing it access to tissue compartments beyond the liver. The most notable extra-hepatic cellular reservoir is peripheral blood mononuclear cells or PBMCs, e.g., B and T lymphocytes and monocytes, although it is controversial as to whether active viral replication occurs in these cells or if the presence of virus is due to passive diffusion (Bernardin et al, 2008; Chary et al, 2012; Fujiwara et al, 2013; Radkowski et al, 2005; Ray and Thomas, 2010). After incorporation into an endosome, the decreased pH causes a conformational change in viral envelope proteins, resulting in fusion with the endosomal membrane and extrusion of viral RNA into the cytoplasm at the rough endoplasmic reticulum where it is translated by host ribosomes.…”
Section: Methodsmentioning
confidence: 99%
“…The hypervariable region is in E1 and E2 and the lowest variability is found in the 5' untraslated region (UTR) containing RNA secondary structures which are required for replication and translation functions. The lack of proofreading activity of RNA-dependent RNA polymerase causes sequence variability and the nucleotide misincorporation rate is approximately 10-3 base substitutions per genome site per year (Bhatti et al, 1995;Fujiwara et al, 2012). All HCV genotypes are pathogenic and hepatotropic and influence on the rate of progression to cirrhosis and HCC.…”
Section: Hcv Epidemiologymentioning
confidence: 99%
“…According to E2 function, E2 can bind especially to immune receptor CD81 (Cluster of Differentiation 81) as a main receptor for this virus, high density lipoprotein (HDL) and also scavenger receptor (type B class 1) protein (SRB-1) but the interaction of E2 protein due to viral entry with Mannose binding proteins (DC-SIGN and L-SIGN) is not known. E2 has two hypervariable regions (HVR) which are under selection for mutation and they are targets for neutralizing antibodies (Fujiwara et al, 2012). The genetic heterogeneity of the HVR helps virus to evade the immune system.…”
mentioning
confidence: 99%